Comparison of Depression and Anxiety Scores in Multi/Nulliparous Women who have Undergone Dilatation and Curettage: Comparison of Depression and Anxiety Scores in Undergone Dilatation and Curettage - Yalcin Bahat, Pinar; Turan, Gökçe; Topbaş Selçuki, Nura Fitnat; Çakmak, Kübra; Kaya, Cihan (Acta Biomedica Atenei Parmensis, 2022)
SummaryAim: To demonstrate the duration of negative psychological effects of elective curettage on both nulliparous and multiparous women and to determine the association between parity and post-abortion depression and anxiety.Materials and Methods: A total of 168 women who applied to our reproductive health clinic for elective abortion were included in this prospective study. 84 nulliparous and 84 multiparous women were asked to fill out Beck Depression Inventory (BDI-II) and Beck Anxiety Inventory (BAI-II) forms by a psychiatrist at their pre-abortion consultation and at 3 months follow-up. A thorough anamnesis with demographic data of each patient was recorded at initial consultation.Results: Depression and anxiety measurements in both groups significantly decreased at the end of the 3 months follow-up. The mean depression value in nullipara group decreased from 24.2 ± 5.8 to 9.4 ± 3.3 and anxiety from 23.5 ± 3.7 to 8.8 ± 2.5. In the multipara group, the mean depression score decreased from 15.7 ± 4.0 to 7.3 ± 2.3, and anxiety from 15.9 ± 4.0 to 7.9 ± 2.3. A significant decrease in both depression and anxiety scores could be observed in both groups.Conclusion: Although the severity of depression and anxiety varies between multiparous and nulliparous individuals, this study showed that both depression and anxiety scores return to normal values by the end a 3 months follow-up period.